The Effect of Exercising on the Decrease Back Pain: A Systematic Review - Borko Katanic; Predrag Ilic; Lora Kostic; Aleksandar Stojmenovic; Mima Stankovic; Manja Vitasovic (University of Montenegro, Faculty for Sport and Physical Education, Montenegrin Sports Academy, 2021)
The aim of this study was to determine the impact of exercising on the back pain. Tools used for the literature review are electronic databases: Google Scholar, PubMed, Medline, Mendeley, for the time period from 2010. to 2019. After the selection of papers regarding the criteria, 20 studies that suit the needs of this systematic review were selected. Therapeutic training for relieving back pain is very heterogeneous, a total of 12 different therapeutic exercise programs were conducted. The most used programs are pilates and conventional (traditional) program for relieving back pain, followed by stabilization exercises, as well as other methods, such as: sling method, motor control exercises, stretching exercises, segment stabilization, as well as combined programs. Based on the analysis of the research conducted so far, it has been determined that exercising has positive impact in decreasing pain intensity and the level of disability, on the increase of the maximum strength, durability and trunk flexibility, as well as on the improvement of the overall health related functionality of patients with back pain. It has been concluded that program of exercises has a multiple positive impact on the health of patients with the chronical back pain and that exercising to these patients is, therefore, recommended.